2020
DOI: 10.3390/molecules25071675
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Synthesis of Benzothiazole Compounds Related to Green Chemistry

Abstract: Benzothiazoles have played an important role in the field of biochemistry and medicinal chemistry due to their highly pharmaceutical and biological activity. The development of synthetic processes is undoubtedly one of the most significant problems facing researchers. In this review paper, we provided recent advances in the synthesis of benzothiazole compounds related to green chemistry from condensation of 2-aminobenzenethiol with aldehydes/ketones/acids/acyl chlorides and the cyclization of thioamide or carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 73 publications
0
32
0
1
Order By: Relevance
“…Owing to the huge pharmacological significance associated with benzothiazole motif, several review articles were written on their synthetic methodologies and therapeutic potential [90–181] . We searched across various Web Engines such as SciFinder, Google Scholar, ScienceDirect and Pubmed with the keywords solid‐supported/Heterogeneous synthesis of benzothiazoles.…”
Section: Comparison With Earlier Published Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the huge pharmacological significance associated with benzothiazole motif, several review articles were written on their synthetic methodologies and therapeutic potential [90–181] . We searched across various Web Engines such as SciFinder, Google Scholar, ScienceDirect and Pubmed with the keywords solid‐supported/Heterogeneous synthesis of benzothiazoles.…”
Section: Comparison With Earlier Published Articlesmentioning
confidence: 99%
“…published review articles on the developments of benzothiazole‐based scaffolds of pharmacological importance. Khokra et al., [129] Liu et al., [130] Gandhi et al., [131] Mene and Kale, [132] Bhoi et al., [133] Henary et al., [134] Malik et al., [135] Mathur, [136] Gupta and Rawat, [137] Shaista and Amrita, [138] Dadmal et al., [139] Gao et al., [140] Prajapati et al., [141] Kai et al., [142] Achaiah et al., [143] Bhat and Belagali, [111] Midhula et al., [144] Nangare et al., [145] Banerjee et al., [146] Jiang et al., [147] Ning et al., [148] Weekes and Westwell, [149] Li and Wang, [150] Yadav et al., [151] Ulrich, [152] Li et al., [153] Jaiswal et al., [154] Pandey and Pal, [155] Zhu et al., [156] Cheng et al., [157] and Zhilitskaya et al [158] . published reviews focusing on the protocols employed for the synthesis of benzothiazole derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Phản ứng kiểu Willgerodt-Kindler với tác nhân oxy hóa lưu huỳnh được phát triển để ngưng tụ đóng vòng oxy hóa và được áp dụng để tổng hợp các 2-benzoxazol từ o-aminophenol và xeton [17]. Gần đây, các hợp chất benzothiazole được tổng hợp từ o-aminothiophenol với andehit/xeton/axit/acyl clorua và đóng vòng với thioamide hoặc carbon dioxide [18]. Trong nghiên cứu này chúng tôi công bố một phương pháp mới đơn giản để tổng hợp các dẫn chất khung 1,3-benzothiazol đi từ các dẫn chất của o-aminothiophenol và acetophenon.…”
Section: Mở đầUunclassified
“…It has also been found that the selective functionalization of benzothiazole with diverse substituents grows their range of action in many fields. Various recent synthetic processes have been developed for the preparation of benzothiazole compounds associated with green chemistry 8 . Benzothiazole derivatives linked with some heterocyclic ring such as thiadiazole have a high biological activity against some bacterial 9 .…”
Section: Introductionmentioning
confidence: 99%